IN THE MATTER OF THE FEMALE MIND: AN ANALYSIS OF THE SUPREME COURT OF CANADA’S APPROACH TO WOMEN AND MENTAL HEALTH - Bay, Odelia (Critical Disability Discourses, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->According to the Supreme Court of Canada’s most recent equality law ruling in Withler v. Canada (Attorney General) (2011), considerations of context must be central to a discrimination analysis. As the jurisprudence evolves, discrimination cases in Canadian courts are becoming increasingly complex and some legal experts predict that we will see a rise in the number of disability rights claims. To date, very few cases involving women and mental health have made their way up to Canada’s highest court. This paper uses a gendered analysis of disability to examine three Supreme Court of Canada decisions: University of British Columbia v. Berg (1993), Winnipeg Child and Family Services (Northwest Area) v. G. (D.F.) (1997), and Gosselin v. Québec (Attorney General) (2002). The results indicate that in cases where gender and mental health intersect, the Court is unwilling or unable to deal with issues of intersectionality in order to recognize the gendered experience of mental illness. Yet, the Court continues to point to one of these cases, Gosselin, as an example of how to get the contextual analysis right. When it comes to women and mental health, it appears that equality and justice may continue to give way to decontextualization and stereotype.